Teoria da Educação - Contributos Ibéricos - João Boavida (Ensino, 2007)
Education has always been a determining factor in the life of men and societies, but it has today acquired enormous relevance, becoming one of the great themes of the moment with importance not only for the present but also for the future.ALT_QUEBRA_LINHAMany different academic subjects contribute to education, ranging from the social and human sciences to the empirical sciences, while the social, cultural, spiritual and moral fund represented by education continues to flow incessantly like a deep river which, despite the winds and turbulence that agitate and perturb its surface. The problems that concern education today, like scientific information and empirical research which can clarify it, cannot dispense with theoretical analyses to arrive at new forms of understanding that are as complex as they are problematic and difficult as are the educational subjects.ALT_QUEBRA_LINHAThis book brings together multiple perspectives on education by professors and researchers from Portugal and Spain in the domain of theory and philosophy of education. Bringing together representatives of 22 universities in the Iberian Peninsula, these studies reflect a multiplicity of theoretical approaches to education, giving a global view of what is thought in the geographical and cultural context of Western Europe. It is, therefore an excellent occasion to deepen our knowledge of these subjects and look at them from innovative and fertile perspectives.